Revisiting Islamic Economics of Nusantara: Conceptual and Legal Perspectives - Anwar, Moch Khoirul; Febrianto, Nur Fitroh (Universitas Negeri Surabaya, 2020)
The development of Islam in Indonesia is inseparable from the economy because Islam initially came to Indonesia through trade. The teachings of Islam are embedded through economic activities such as in commerce and agriculture, although not uses Islamic terms specifically. As a result, many people are not aware that their economic activity becomes part of the implementation of the Islamic economics concept. Therefore, this paper aims to examine the implementation of Islamic economics in this country, both in terms of conceptual and formal legal practice implemented by the community. This study based on library research that focused on studying a variety of works of literature about the Islamic economic system and its implementation in Indonesia. Interviews and observation also collect the data to farmers and cattle ranchers that have taken as the sample. Furthermore, the data analysis employs a content analysis method to identify the specific characteristics of the information when data had been collected. The results of this study indicate that some of the Islamic economics concepts has been applied in the Indonesian daily economy activities. This reflects the manifestation of the 33rd Article of the Indonesian Constitution 1945 that emphasizes economic built by the cooperations and kinship principle. In the society who do farming and animal husbandry, for example, people implements